2019
DOI: 10.1186/s12889-019-7698-9
|View full text |Cite
|
Sign up to set email alerts
|

People with activity limitations’ perceptions of their health condition and their relationships with social participation and experienced autonomy

Abstract: BackgroundPeople with activity limitations participate less in society, which may be due to both societal barriers and personal factors. The aim of this study was to examine the role of one specific personal factor, namely the perceptions that people have of their health condition. We hypothesized that perceptions of more personal control and less negative consequences increase the likelihood of participation in social activities and of experiencing autonomy in participation.MethodsSurvey data of 1681 people w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…The perception of the participants’ health condition is important. A study by Meulenkamp et al has shown that people with activity limitations participate less in society, and if their limitation is long-lasting, they are more likely to participate in volunteer and club activities 47. Fancourt et al revealed findings that show that poor mental health is a barriers for engagement in arts activities 48.…”
Section: Discussionmentioning
confidence: 99%
“…The perception of the participants’ health condition is important. A study by Meulenkamp et al has shown that people with activity limitations participate less in society, and if their limitation is long-lasting, they are more likely to participate in volunteer and club activities 47. Fancourt et al revealed findings that show that poor mental health is a barriers for engagement in arts activities 48.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, note that studies of the patient’s perspective [ 3 , 4 ] agree that patients with PAH often describe feeling insecure, isolated, and as living with an invisible disease, therefore, to fully eliminate the impact of PAH on a patient’s life, complex interventions in addition to medical treatment of the underlying disease are important, and therefore our treatment approach has the potential to support an individual living with PAH to cope with illness. The observed benefits of the investigated program to improve the perceived chance of participation in activities related to frequency of social contacts in the PAH patients might be due to the change in the perception about their health condition and the improved sense of self-control abilities, as is approved relevant correlations between these factors in other studies [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…As with other health conditions, women commonly have beliefs (also called representations) about dysmenorrhea (Adrián-Arrieta, & Casas-Fernández de Tejerina, 2018;Meulenkamp et al, 2019;Stuifbergen, Phillips, Voelmeck, & Growder, 2006). It is unknown how the beliefs women hold regarding their dysmenorrhea differ for women in different symptom-based phenotypes.…”
Section: Introductionmentioning
confidence: 99%